Conflict Sensitive Adaptation Governance (CSAG): Towards a theoretical framework for integrating climate, peace, and security into adaptation policy - Schapendonk, Frans; Medina, Leonardo; Jaskolski, Martina (2024)
This conceptual and methodological note introduces a conceptual framework designed to assess multi-scalar climate adaptation policy instruments by gauging the extent to which they consider linkages between climate, peace and security. The purpose of this methodology is to assess whether policy instruments – and the activities and operations enacted within them - are intentionally formulated, implemented, and evaluated with regard to their effectiveness in mitigating conflict and societal instability risks, and to contribute to sustainable peacebuilding efforts.